Sistem Informasi Penjualan Kayu Jati Berdasarkan Volume (Meter Kubik) pada CV. Jati Mulyo Berbasis Web - Ariyanto, Ariyanto, Nurgiyatna, S.T., M.Sc., Ph.D (2016)
CV. Jati Mulyo is a company which relates on the sale sector of the sawing's teak. The selling system is still using conventional model to do the selling of the teak wood. A consumer who looks for teaks must come directly to the storeroom of CV. Jati Mulyo to get the teak wood. Therefore, its selling is less maximal for marketing scope. To cope with the problem, so that it will be designed information system of the teak's wood selling based on volume (metre cubic) by online for marketing scope in order to help the extend of marketing scope, increase the advantages for the company and help the consumer to get information about the teak's price based on the its type. The selling information system will be established by using PHP, CSS, Javascript, and MySQL. Metode used for this reasearch is waterfall method, it has some stages that are necessary analysis, design system, implementation, test, and maintenance. This information system will make easier for consumer of getting information about teak wood price based on its category and its type. From the result of the research, admin can manage website management (it covers data of the teak wood and its price). This website is very helpful on promote the teak production, it can be seen from questionare result as 81% that agrees with having the selling information system of the teak wood based on volume (metre cubic).